Circulating Levels of miR-574-5p Are Associated with Neurological Outcome after Cardiac Arrest in Women: A Target Temperature Management (TTM) Trial Substudy. (2nd June 2019) - Boileau, Adeline; Somoza, Antonio Salgado; Dankiewicz, Josef; Stammet, Pascal; Gilje, Patrik; Erlinge, David; Hassager, Christian; Wise, Matthew P.; Kuiper, Michael; Friberg, Hans; Nielsen, Niklas; Devaux, Yvan; et al.
Abstract : Purpose. Postresuscitation neuroprognostication is guided by neurophysiological tests, biomarker measurement, and clinical examination. Recent investigations suggest that circulating microRNAs (miRNA) may help in outcome prediction after cardiac arrest. We assessed the ability of miR-574-5p to predict neurological outcome after cardiac arrest, in a sex-specific manner. Methods. In this substudy of the Target Temperature Management (TTM) Trial, we enrolled 590 cardiac arrest patients for which blood samples were available. Expression levels of miR-574-5p were measured by quantitative PCR in plasma samples collected 48 h after cardiac arrest. The endpoint of the study was poor neurological outcome at 6 months (cerebral performance category scores 3 to 5). Results. Eighty-one percent of patients were men, and 49% had a poor neurological outcome. Circulating levels of miR-574-5p at 48 h were higher in patients with a poor neurological outcome at 6 months (p < 0.001 ), both in women and in men. Circulating levels of miR-574-5p were univariate predictors of neurological outcome (odds ratio (OR) [95% confidence interval (CI)]: 1.5 [1.26-1.78]). After adjustment with clinical variables and NSE, circulating levels of miR-574-5p predicted neurological outcome in women (OR [95% CI]: 1.9 [1.09-3.45]), but not in men (OR [95% CI]: 1.0 [0.74-1.28]). Conclusion. miR-574-5p is associated with neurological outcome after cardiac arrest in women.